1986
DOI: 10.1029/jd091id05p05347
|View full text |Cite
|
Sign up to set email alerts
|

The CH3CHO‐NO3 reaction and possible nighttime PAN generation

Abstract: Kinetic studies have been made of the CH3CHO-NO 3 reaction in dilute mixtures of CH3CHO, NO•_, and N,_O5 in synthetic air at 700 torr and room temperature. During the course of the reaction, reactant and product analyses were made in situ, using long path length Fourier transform infrared spectroscopy. The major products of the reaction for these conditions are HONOr_ and CH3COO•_NO•_. All evidence suggests that the first step in the reaction sequence, NO 3 + CH3CHO• HONO,_ + CH3CO , proceeds with a rate const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Another source of nighttime free radicals in the troposphere, the NO 3 radical, has been suggested in a number of experimental and theoretical studies [Japar and Niki, 1979;Stockwell and Calvert, 1983;Pitts et al, 1984;Cantrell et al, 1985;Calvert et al, , 1994Killus and Whitten, 1985;Cantrell et al, 1986;Platt et al, 1990;LeBras et al, 1993]. NO 3 has been observed directly in the troposphere in a number of field studies [e.g., see Noxon et al, 1980;Noxon, 1983;Platt et al, 1980Platt et al, , 1984Yvon et al, 1996].…”
Section: Possible Role Of No3 Chemistry In Nighttime Peroxy Radical Gmentioning
confidence: 99%
“…Another source of nighttime free radicals in the troposphere, the NO 3 radical, has been suggested in a number of experimental and theoretical studies [Japar and Niki, 1979;Stockwell and Calvert, 1983;Pitts et al, 1984;Cantrell et al, 1985;Calvert et al, , 1994Killus and Whitten, 1985;Cantrell et al, 1986;Platt et al, 1990;LeBras et al, 1993]. NO 3 has been observed directly in the troposphere in a number of field studies [e.g., see Noxon et al, 1980;Noxon, 1983;Platt et al, 1980Platt et al, , 1984Yvon et al, 1996].…”
Section: Possible Role Of No3 Chemistry In Nighttime Peroxy Radical Gmentioning
confidence: 99%
“…The measured HO rate constants were paxtitioned so that one-half of the addition occurred at the two terminal positions in isoprene. In consideration of tl-and g-pinene, addition was assumed to occur exclusively as shown in (29) For curves 1-5, (Z and B are 1.3, 0; 1.3, 0.1; 1.3, 0.2; 1.3, 0.3; 1.3, 0.4, respectively In view of theoretical expectations, the generation of peroxy radicals through nighttime chemistry [Stockwell and Calvert, 1983;Cantrell et al, 1985Cantrell et al, , 1986] was expected in this study. As we indicated previously, the current radical measurements could be influenced by a measurable contribution from PAN, especially during the nighttime hours.…”
Section: (Li) D[r202]/dt = 0 = [Ho][isoprene]k12/ + [Ho][mvk]k•8 + [mentioning
confidence: 99%
“…CH3SO2 + NO2 CH3S03 + NO (20) The competition between reactions (17) and (19), which determines the SOZto-CH3S03H product ratio, was recently proposed by Yin et al [37]. In their study, Yin et al used a detailed mechanism to simulate DMS and SO2 temporal profiles observed at night in an outdoor chamber containing NO,-DMS-air mixtures.…”
Section: Imentioning
confidence: 99%